ASSESSMENT OF THE STATUS OF THE HEALTH OF WORKERS ROLLING PRODUCTION FOR THE INCIDENCE - Хамитов, Тулеген Нургалиевич (Medicine in Kuzbass, 2018)
Objective. The health condition of workers of rolling production for the incidence of workers rolling production of JSC «ArcelorMittal». The purpose of the work – hygienic assessment of morbidity with temporary disability of workers of rolling production. Methods. Assessment of workers ’ health based on the results of the analysis of morbidity with temporary incapacity for work (TIW). Results. It was revealed that workers have high values of morbidity with temporary disability, as in cases and days of incapacity to work, their values, in accordance with the classification of the highest level. Of the production workshops of the level of harm in the first place plate rolling shop №1 (hot rolling). Women suffer more often than men. The most unfavorable are the age ranges of under 30 years and 30-39 years, the related ranges of 5-9 years and 15-19 years. The highest incidence is noted in workers of the main professions. In the structure of morbidity in all plants occupy a leading place diseases of the respiratory system and the musculoskeletal system. Conclusions. Unfavorable factors of production environment have a negative impact on the performance of health workers, which is reflected in the high values of morbidity with temporary disability.